The relationship between gratitude and adolescents’ prosocial behavior: A moderated mediation model - Zhang, Ding (Frontiers in Psychology, 2022)
The development of prosocial behavior is an important embodiment of youth socialization. Cultivating adolescents’ prosocial behaviors can be beneficial to individuals form correct outlook on life and values, and has a profound impact on promoting the harmonious development of society. This paper constructs a model to explain the mediating role of sense of meaning in life between gratitude and prosocial behavior and the moderating role of self-esteem in the mediating path. From the analysis of the data of 2,735 questionnaires utilizing SPSS 22, it can be concluded that: (1) gratitude has a significant positive effect on prosocial behavior; (2) sense of meaning in life plays a mediating influence on the relationship between gratitude and prosocial behavior; (3) self-esteem has a moderating impact on relationship between sense of meaning in life and prosocial behavior, which means that adolescents with high self-esteem experience a stronger positive effect of a sense of life’s meaning on their prosocial behavior. These findings not only add to research on the relationship between gratitude and prosocial behavior, but also provide ideas for improving adolescent prosocial behavior.